PENGARUH VARIASI SUHU PENCAMPURAN DAN PEMADATAN AGREGAT BATU PECAH MADURA (DESA ASEM JARAN KECAMATAN BANYUATES KABUPATEN SAMPANG) PADA CAMPURAN ASPAL PANAS (HOTMIX) ASPHALT CONCRETE WEARING COURSE (ACWC), TERHADAP KARAKTERISTIK MARSHALL - Taurina Jemmy Irwanto (LPPM Universitas Merdeka Madiun, 2019)
AbstractThe mixing temperature has a role in the asphalt smelting process against aggregate, while the compaction temperature has a depth in the density level of the hot asphalt mixture. The better the mixing and compaction process, the better the mixing and compaction process, the better the performance of the asphalt mixture, the better the performance of the asphalt mixture, the better the paved mixture is planned according to the general specifications of Bina Marga 2010. The mixture of mixtures used is Concrete Wearing Course (ACWC). In this study aims to determine the effect of variations in mixing temperature and compaction on the mixture ACWC hot asphalt using broken stone Asem Jaran Distric Banyuates Sampang. Temperature variations used are 160/1460C, 170/1560C, 180/1660C , 190/1760C and 200/1860C with asphalt content 5,2%, 5,7% dan 6,2%. The test uses the Marshall test method by looking for the charcteristic values of Marshall. Based on the results of testing in the laboratory, it was found an increase in the value of Marshall characteristics from variations in temperature 160/1460C to 170/1560C temperature variations and to decrease the test result of Marshall characteristics values at a temperature variation of 180/1660C , 190/1760C and 200/1860C so that it was concluded that the use of mixing temperature and optimum compaction at a temperature variation of 170/1560C. Keywords: Temperature, Temperature Variation, Marshall Test, Asphalt concrete Wearing Course (ACWC).